Manifestations of and perceptions on love among Filipino college students - Quejada, Andrea Celine Celestino; Reyes, Nicole Andrea; Juadiong, Lillian L. (2011.)
This paper aimed to understand what Filipino college students perceive when they encounter love. This exploratory study employed survey forms to gather data regarding the manifestations of love, and face to face interviews to explore the perceived nature of love among 120 Filipino college students, of which 60 were female and 60 were males. Out of the 120 respondents, 40 agreed to be interviewed. Among these 40 respondents, half consisted of females, while the other half were males. Initially, random students were selected as respondents but purposive sampling was utilize to maintain a balance between gender and year levels. The results showed that Gary Chapman's Five Love Languages (Quality Time, Words of Affirmation, Acts of Service, Physical Touch, and Gifts) are ways in which Filipino college students manifest love. Gender differences were investigated as far as manifestations of love were concerned. The only category in which a significant difference was found that males favoured physical touch as an expression of love more than females did. Interview questions about experiences of love were formulated by the researchers. The responses were then categorized under the themes Crush, Infatuation, Love, and Passion, as defined by the researchers. It was found that majority of Filipino college students' thoughts and perceptions on love fall under the category of Love. To majority of the respondents, it was found that love is one that calls one to make sacrifices for another person, and to experience happiness in doing so. The study may be used as a springboard to other studies regarding manifestations of and perceptions on love among adolescents.
Thesis (BSFLCD)--University of the Philippines Diliman.
Keywords: Love -- Philippines